2008
DOI: 10.1177/0021998308088619
|View full text |Cite
|
Sign up to set email alerts
|

Damage Analysis of a Type 3 Cryogenic Propellant Tank After LN2 Storage Test

Abstract: The application of composites to cryotanks has been one of the major concerns for lightweight launch vehicles. In this study, a prototype of a Type 3 cryotank was fabricated with the composite developed for cryogenic application and aluminum liner, and the cryogenic conditions were applied by filling the prototype with liquid nitrogen and then pressurizing it with gaseous nitrogen. During the experiment, delamination inside the cryotank happened. This article describes several attempts made to investigate fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…From aerospace to automotive applications, practical design and analysis of filament-wound composite vessels have been widely based on the classical lamination theory [5][6][7][8] or a finite element method associated with a macroscopic failure criterion. [9][10][11][12][13] More recently, a continuum damage mechanics approach has been used by Liu and Zheng 14 in a finite element formulation to predict progressive damage due to different mechanisms that lead to the bursting of a hydrogen storage composite vessel.…”
Section: Introductionmentioning
confidence: 99%
“…From aerospace to automotive applications, practical design and analysis of filament-wound composite vessels have been widely based on the classical lamination theory [5][6][7][8] or a finite element method associated with a macroscopic failure criterion. [9][10][11][12][13] More recently, a continuum damage mechanics approach has been used by Liu and Zheng 14 in a finite element formulation to predict progressive damage due to different mechanisms that lead to the bursting of a hydrogen storage composite vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials, which have high specific strength and stiffness, and low coefficients of thermal expansion (CTEs), have recently been investigated for their applicability to propellant tanks. Under cryogenic environment, composite materials with different CTEs between its reinforcing fibers and matrix cause extreme thermal stress, which leads eventually to microcracks in the polymer matrix (Kang et al, 2008;Nair and Roy, 2006). As the microcrack density increases, they can propagate in the thickness direction and emerge as a mechanism for leakage as well as mechanical degradation of the tank structure (Kang et al, 2008).…”
Section: Rocket Propellant Tanks/fuel Tanksmentioning
confidence: 99%
“…In some cases, a Type 3 composite tank is generally preferred to a Type 4 tank. A Type 3 is a composite tank that is lined with metal to maintain permeability, and a Type 4 is a tank that is fabricated only with composite materials (Kang et al, 2008). Hoop and helical layers of composite are wound onto the metal liner in the Type 3 tank structure.…”
Section: Rocket Propellant Tanks/fuel Tanksmentioning
confidence: 99%
See 1 more Smart Citation
“…Work on the design and analysis of composite cryo-tanks has intensified since the failure of the NASA/Lockheed X-33 RLV fuel tank [5], where fuel leakage occurred due to cryogenically induced damage in the composite tank wall. Subsequent experimental and theoretical analyses of cryo-tanks [6,7] have found that, unlike traditional COPVs, the thermal stresses induced by cryogenic loading are the main design consideration and play a critical role in damage formation. In addition, the role of material quality and processing conditions on damage initiation remain understudied [8,9], particularly for advanced thermoplastic composites such as CF/PEEK, which are increasingly used in conjunction with novel processing techniques such as automated tape laying (ATL) for the manufacturing of large structures.…”
Section: Introductionmentioning
confidence: 99%